The role of arbuscular mycorrhizal fungi in the biotransformation of coal and application in dump rehabilitation - Mukasa-Mugerwa, Thomas Tendo (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2007)
Fundamental processes underpinning the biotransformation of coal by fungal biocatalysts have been intensively investigated, however, limited large-scale industrial applications using such systems have been reported. The un-anticipated sporadic growth of Cynodon dactylon on the surface of un-rehabilitated discard coal dumps has been noted and this was found to be coupled with the breakdown of coal into a humic soil-like material in the top 1.5 metres of the dumps. Extensive fungal growth was observed to be associated with the Cynodon dactylon root system and examination of plant roots indicated the presence of mycorrhizal fungi. Analysis of the Cynodon dactylon plant roots around which coal biotransformation was occurring confirmed the presence of arbuscular mycorrhizal colonisation with the species Glomus clarum, Paraglomus occultum, Gigaspora gigantea and Glomus mosseae identified to be associated with the plants. Further molecular characterisation of non-mycorrhizal rhizospheric fungi showed the presence of fungal species with coal-degrading capabilities that most likely played a role in the coal biotransformation observed. The discard coal dump environment was simulated in pot and column studies and coal biotransformation was reproduced, with this process enhanced by the addition of mycorrhizal and non-mycorrhizal rhizospheric fungal inocula to the environment. Mycorrhizal and non-mycorrhizal species in the inoculum were re-isolated from the simulated environment fulfilling a number of Koch's postulates and indicating a causal role in the biotransformation of coal. An inversion of conventional mycorrhizal colonisation was demonstrated in this system with reduction in extraradicular presence and an increase in intracellular colonisation compared to soil controls. A descriptive model was formulated suggesting a two-part fungal system involving organic carbon and nutrient exchange between the plant, mycorrhizal fungi and non-mycorrhizal coal-degrading rhizospheric fungi ultimately resulting in the biotransformation of coal. The biotransformation observed was comparable to reports of "rock-eating fungi" . Results suggest that the biological degradation of coal in situ with the production of a soil-like substrate could provide a feasible method of discard coal dump rehabilitation as well as provide a humic-rich substrate that can be utilised in further industrial applications.
Keywords: Vesicular-arbuscular mycorrhizas; Mycorrhizal fungi; Fungi -- Biotechnology; Bermuda grass; Coal mines and mining -- Environmental aspects; Acid mine drainage